1997
DOI: 10.1073/pnas.94.7.3052
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 8-stimulated phosphatidylinositol-3-kinase activity regulates the migration of human neutrophils independent of extracellular signal-regulated kinase and p38 mitogen-activated protein kinases

Abstract: Chemoattractants and chemokines, such as interleukin 8 (IL-8), are defined by their ability to induce directed cell migration of responsive cells. The signal transduction pathway(s) leading to cell migration remain ill defined. We demonstrate that phosphatidylinositol-3-kinase (PI3K) activity, as determined by inhibition using wortmannin and LY294002, is required for IL-8-induced cell migration of human neutrophils. Recently we reported that IL-8 caused the activation of the Ras͞Raf͞extracellular signal-regula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
192
2
2

Year Published

1998
1998
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 299 publications
(213 citation statements)
references
References 60 publications
17
192
2
2
Order By: Relevance
“…In contrast, the role of the MAPK pathways for chemotaxis is less clear, although its activation via chemokine receptors is well documented [33,[47][48][49]. One publication even showed that the MAPK pathways are dispensable for inducing a chemotactic response in human neutrophils [50]. In addition, it was shown that elevations of intracellular calcium are not necessary for directional migration of mouse neutrophils [36].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the role of the MAPK pathways for chemotaxis is less clear, although its activation via chemokine receptors is well documented [33,[47][48][49]. One publication even showed that the MAPK pathways are dispensable for inducing a chemotactic response in human neutrophils [50]. In addition, it was shown that elevations of intracellular calcium are not necessary for directional migration of mouse neutrophils [36].…”
Section: Discussionmentioning
confidence: 99%
“…9,10 One study showed that replacement of 2 tyrosine residues within the PI3K-binding sites of the PDGF ␤-receptor causes a loss of chemotactic response to PDGF-BB 21 ; however, another study demonstrated that PI3K inhibitors did not inhibit chemotaxis in SMCs and Swiss 3T3 cells. 22 In the present study, the inhibition of PI3K by wortmannin partially reduced PDGF-BB-induced SMC migration.…”
Section: Discussionmentioning
confidence: 99%
“…8 It has been previously reported that activation of the phosphatidylinositol 3Ј-kinase (PI3K) pathway is a rapid response to platelet-derived growth factor (PDGF), one of the most potent chemoattractants for SMCs, and is implicated in cellular motility, such as actin reorganization and membrane ruffling, in several cell types, including SMCs. 9,10 Moreover, it has been demonstrated recently that activation of mitogen-activated protein kinase (MAPK) pathways also plays a role in cell migration. Specifically, it has been reported that p38 MAPK , one of the MAPK pathways, may mediate the migratory action of tracheal SMCs in response to PDGF.…”
mentioning
confidence: 99%
“…In neutrophils, inhibiting the PI 3-kinase activity has been shown to decrease the downstream activation of the MAPK signaling cascade, e.g., activation of MEK, ERK, and MAPK [20,43,67]. In the study by Avdi and co-workers [43], the chemoattractant-induced activation of MEK kinase, MEK1, MEK2, as well as MAPK was shown to be inhibited by wortmannin while they proved to be independent of PI 3-kinase when activated by PMA.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of PI 3-kinase is an early event in neutrophil responses to chemoattractants and has been shown to participate in intracellular signaling, leading to processes such as chemotaxis, actin polymerization, degranulation, and adhesion [17,[19][20][21][22][23]. The PI 3-kinase is also involved in the signaling leading to NADPH-oxidase activation in response to formylmethionyl-leucyl-phenylalanine (fMLP [14,17,21,24]).…”
Section: Introductionmentioning
confidence: 99%